Competition in collecting return products between manufacturer and retailer under quality improvement and greening of products in the closed-loop supply chain - Mohsen Shahriari; Maryam Gholami (مدیریت تولید و عملیات, 2022)
Purpose: In this paper, the competition for the collection of electronic and electrical waste between the manufacturer and the retailer has been discussed to recover them, taking into account the improvement of the quality and greening of the collected products to increase the level of customer satisfaction and increase profits, and reducing dangerous effects on the environment. For this purpose, a closed two-loop supply chain has been designed with three models. A centralized model has been considered for cooperation in the collection channel of the entire chain with the integration of the manufacturer and retailer and two decentralized models for competition in the collection of returned products between the manufacturer and retailer with two scenarios. In the first scenario, the impact of improving the quality and greening of manufactured products of a decentralized two-person model has been analyzed, consisting of a manufacturer and a retailer, and its performance compared to a centralized model. In the second scenario, the profits-sharing agreement between a retailer and a manufacturer has been used in the decentralized model. Design/methodology/approach: The decisions of product quality improvement have been investigated in a simple dynamic environment and consumer preferences have been considered for new and remanufactured products as a performance of new product quality. In the developed model, the topic of quality and greening has been given, and the demand functions and profit functions have been written accordingly considering two demand functions for the manufacturer and retailer, and also two profit functions for the manufacturer and retailer. Mathematica software has been used for solving problems and also graphs related to sensitivity analysis. The discussion has been drawn and the analysis related to the profit functions of the manufacturer and the retailer has been done regarding the parameters. Findings: The results indicated that the manufacturer preferred to work with the retailer in a non-competitive manner. The retailer used the first scenario because due to its profit. The retailer’s profit was more concentrated in the second scenario. The proposed approach was suggested to be applied to multiple manufacturers and retailers in future studies. It was also recommended to consider the storage and inventory costs for the collection products and to estimate the duration in which, they can stay in the manufacturer's warehouse with no costs increase. Another suggestion was to consider the demand with different functions or with a stochastic variable. Research limitations/implications: The limitations of this research are: i) determining the quality level of collected products; ii) the location for remanufacturing by the manufacturer and recycling by the retailer; iii) sales estimate; iv) forecasting the number of products and types of products that have been collected; v) estimating consumer demand for remanufactured products; and vi) grading the greening of the collected products. Practical implications: In general, economic profitability is considered the main driving factor for the entry of original equipment manufacturers and independent remanufacturers of the remanufacturing industry. According to the results, manufacturing companies can remanufacture the valuable wastes after retailers collected them and then determine their quality level. By increasing the quality and production of greening products, they have entered the competitive market and have offered products at a lower cost and more profit, when a centralized model was used. Social implications: In today's society, one of the important issues is environmental sustainability. In this regard, the remanufacturing of returned products and the greening of products by the manufacturer have reduced the use of raw materials, saved energy, and reduced air pollution. In this paper, the subjects of competition for the collection and recycling of electronic and electrical waste (i.e, medical equipment, lighting devices and lamps, all kinds of audio and video equipment, IT equipment and household electrical appliances) between the manufacturer and the retailer, the improvement of the quality and greening of the collected products to increase the level of customer satisfaction/profits, and reducing dangerous effects on the environment were discussed. Originality/value: This study contributed to the quality improvement of returned products and greening products. Based on this research, product quality decisions are investigated in a simple dynamic environment, and consumer preferences for new and remanufactured products are considered as a function of new product quality. In summary, this research has examined the interactions between improving the quality of remanufactured products and greening.